Saluran Pemasaran Kentang Di Kecamatan Modoinding Kabupaten Minahsa Selatan - Losoh, Miranti; Waney, Nordy Fritsgerald Lucky; Sendow, Martha Mareyke (Sam Ratulangi University, 2023)
This study aims to describe the potato marketing channel and calculate the potato marketing margin in Modoinding District, South Minahasa Regency. This research was conducted for two weeks, namely the third week of July to the fourth week of July 2022. The data collection method used a survey method. Data collection techniques were carried out by interviews using a structured list of questions and followed by observation (observation). The data used are primary data and secondary data. Primary data was collected through interviews based on a questionnaire. Secondary data was obtained from BPS and Agricultural Extension Center. The results of the study found four potato cooking channels in Modoinding District, South Minahasa Regency. The marketing margin received by each marketing channel, namely marketing channel I is IDR 1,500, marketing channel II is IDR 2,500, marketing channel III is IDR 1,500 and marketing channel IV is IDR 2,500. farmer's share is the part received by farmers from the price paid by consumers. farmer's share of each marketing channel, namely marketing channel I by 10 percent, marketing channel II by 0.4 percent, marketing channel III by 0.4 percent and marketing channel IV by 0.3 percent.